The self-efficacy in breastfeeding of women in the prenatal and postpartum: longitudinal study - Janaiana Lemos Uchoa; Andressa Peripolli Rodrigues; Emanuella Silva Joventino; Paulo César de Almeida; Mônica Oliveira Batista Oriá; Lorena Barbosa Ximenes (Universidade Federal de Santa Maria, 2016)
Aim: to compare the averages of self-efficacy scores of women in prenatal and postpartum with the variables of pregnancy, childbirth, postpartum and related to breastfeeding. Method: longitudinal study of Panel type, that evaluated 50 women in prenatal and puerperal in 2011, using the Breastfeeding Self-Efficacy Scale - Short Form and a form with data from the pregnancy, childbirth and the puerperium. Results: statistical significance with the scale were shown by: planned pregnancy; to perform six or more antenatal consultations; to perform the preparation of breasts for breastfeeding; wish to breastfeed the child; participate in Group of pregnant women; vaginal birth in a public hospital; breastfeeding in the first hour of life and exclusively on maternity and on hospital discharge; not having trouble with breast-feeding. Conclusion: several factors may influence in the self-efficacy, being relevant promote breastfeeding such as the prenatal, to encourage this practice and to provide explanations to the mothers about the child's diet